Komunikasi Visual Dakwah Persuasif Pada Akun Instagram @hijabalila Dengan Hashtag #Freedom99persen Dari Perspektif Semiotika Charles Sanders Peirce - Aqilla Padya Hayya; Dewi Anggrayni; Muhammad Fahri (Universitas Pahlawan Tuanku Tambusai, 2022)
Persuasive proselytizing visual communication is the delivery of proselytizing packed with visual content that is conveyed to everyone, made lightly, attractive images, and words that are easy to understand. Preaching in the digital age is a challenge for today's da'i. Social media is one of the media that needs to be utilized. Instagram is becoming one of the most used social media. According to We are Social, social media users in 2022 in Indonesia are 191.4 million in 2021 170 million, an increase of 12.6% and the number of Instagram users in Indonesia in 2022 is 99.15 million people in 2021 85 million people. The purpose of this study was to find out the semiotic analysis of Charles Sanders Peirce and the principle of persuasive proselytizing used on @hijabalila account. This research uses qualitative methods with the type of literature research and the research approach used, namely content analysis. This research analyzes a poster with the theme of #freedom99persen as many as 18 posts each image contains icons, indices, and symbols from Charles Snders Peirce's Semiotics and contains elements of visual communication in the form of illustrations, namely images used to explain something and predominantly red and beige colors have the meaning of courage and life force or the foundation of life. The results of the research from the upload of #freedom99persen poster on the @hijabalila account used elements of icons and indexes used to interpret a meaning of proselytizing in the poster #freedom99persen about courage, obedience, awareness, and love. Then the caption used uses the principles of persuasive proselytizing Qaulan Layyina (preaching meekly), Qaulan Sadidan (preaching with correct speech), and Qaulan Maysuran (preaching with easy-to-understand words). The limitations in this research are due to the large number of posters. It is better for further research to question the perception of followers of instagram accounts @hijabalila in posts uploaded every week with different themes. Keywords: Visual Communication, Da’wah, Instagram, Semiotics